2011
DOI: 10.1177/1066480711417234
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Spousal Attachment, and Marital Satisfaction: A Mediated Model

Abstract: The purpose of this study was to investigate the relationships between mindfulness, spousal attachment, and marital satisfaction. The national sample included 104 married adults aged 19–66. Results indicated partial support for the mediating effect of spousal attachment on the relationship between trait mindfulness and marital satisfaction. Although the relationship between trait mindfulness and marital satisfaction demonstrated in the current study is not the first of its kind, these results provide prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…The findings indicated that greater mindfulness is associated with higher marital quality in both male service members and their partners. In this study we extended previous work on mindfulness and marital quality, which has focused primarily on the intrapersonal associations of mindfulness and marital functioning (Burpee & Langer, 2005;Jones et al, 2011;Wachs & Cordova, 2007), by employing a dyadic approach. We relied on the premises of interdependence theory (Arriaga, 2013;Kelley & Thibaut, 1978), which posits that each partner's characteristics are important to the assessments and behavioral responses to marital situations, which in turn informs partners' evaluations of marital quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings indicated that greater mindfulness is associated with higher marital quality in both male service members and their partners. In this study we extended previous work on mindfulness and marital quality, which has focused primarily on the intrapersonal associations of mindfulness and marital functioning (Burpee & Langer, 2005;Jones et al, 2011;Wachs & Cordova, 2007), by employing a dyadic approach. We relied on the premises of interdependence theory (Arriaga, 2013;Kelley & Thibaut, 1978), which posits that each partner's characteristics are important to the assessments and behavioral responses to marital situations, which in turn informs partners' evaluations of marital quality.…”
Section: Discussionmentioning
confidence: 99%
“…Marital quality refers to feelings and evaluations of spouses about their marital relationship (Glenn, 1990). Previous studies have offered evidence about the direct link between mindfulness and greater marital satisfaction (Burpee & Langer, 2005;Jones, Welton, Oliver, & Thorburn, 2011;Wachs & Cordova, 2007). A recent meta-analysis testing 12 effect sizes from 10 studies indicated that the extent to which marital partners practiced mindfulness across these studies explained 7% of the observed variation in marital quality (McGill, Adler-Baeder, & Rodriguez, 2016).…”
Section: Mindfulness and Marital Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2007, several qualitative and quantitative studies have supported an association between mindfulness and dyadic relationship quality. Specifically, higher levels of mindfulness have been shown to be associated with multiple components of relationship quality: A greater capacity to respond positively to relationship stress (Barnes, Brown, Krusemark, Campbell, & Rogge, 2007); increased empathy and acceptance towards oneself and others (Allen, Bromley, Kuyken, & Sonnenberg, 2009); lower levels of romantic relationship conflict and coparenting conflict around childrearing (Bailie, Kuyken, & Sonnenberg, 2012); enhanced communication quality (Allen et al, 2009; Barneset al, 2007); decreased reactivity and escalation of anger in challenging interactions (Bailie et al, 2012); increased emotional availability (Allen et al, 2009); and increased relationship satisfaction (Barnes et al, 2007; K.C. Jones, Welton, Oliver, & Thoburn, 2011; Wachs & Cordova, 2007).…”
mentioning
confidence: 99%
“…It can be seen that most of the studies in the literature, which focus on the subject, examine mindfulness as experienced through individuals' inner experiences (Frank, Jennings, & Greenberg, 2016). However, research dealing with the effects of mindfulness on interpersonal relationships is quite limited in number (Gillespie, Davey, & Flemke, 2015;Jones, Welton, Oliver, & Thoburn, 2011;Karremans, Schellekens, & Kappen, 2017).…”
Section: Introductionmentioning
confidence: 99%